KEEFEKTIFAN PENDEKATAN BERBASIS GENRE DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI PADA MAHASISWA ANGKATAN 2016/2017 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNRI - Oktari Hendayanti; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is a weak experimental research with one group pretest posttest design. The purpose of this study is to know the effectiveness of Genre Based Approach (GBA) to improve the ability of student class 2016/2017 in writing an exposition text. This approach has been applied in Dokkai Sakubun 5 Course with JF Standard design. There are several student’s writing problems were found during Dokkai Sakubun 5 learning process, i.e the difficulty to compose a story, the difficulty to apply the gramatikal rules while writing, and the difficulty of lack information related to writing topic. Through GBA, students are guided to learn that each type of text is different, in term of social purpose and schematic structure. This study focused on learning to write exposition genre. This genre was chosen due to the course’s indicator to make students able to write opinion according to the theme. Based on the result of the study, it was found that there is an improvement in student’s exposition text writing skill. Student’s essay not only became more structured, but also has a better quality of the content. This was supported by the result of the statistical tests of pretest and posttest data that was conducted.Key Words: Sakubun, Exposition Text, Genre Based Approach (GBA), JF Standard.